El acoso laboral: visibilización del fenómeno y repercusiones en el ambiente de trabajo de las empresas colombianas - Marrugo Puello, Freddy (Ciencias Administrativas, Económicas y Contables, 2017)
The present article seeks to establish criteria in Top Management and Human Development on-the-job to make visible the phenomenon of the mobbing and the generation of alternatives in front of his consequences in the job environment of the Colombian companies. For it initially he provides evidence of his identity and define the mobbing and his demonstrations in the job environments. The analysis of its incidence on the quality of life of the workers straightaway takes effect and lines of action are intended to prevention, mitigation and overcoming of such practices within the organizational climate. By means of a descriptive methodology based in the analysis and documentary revision that includes the bibliographic topical level international, national and local production, in the last ten years. The importance of reflecting on this subject matter comes from the consequences of the mobbing on the job environments and the health of the workers. Essentially he acquires a comprehensive vision about the phenomenon that is correspondingly with the present-day trends of thought related to management and administrative, proposing better tools to guide the practices of organizational development that favor the on-the-job quality of life.